2016
DOI: 10.1037/bul0000077
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and false memory: The context–content paradox.

Abstract: False memories are influenced by a variety of factors, but emotion is a variable of special significance, for theoretical and practical reasons. Interestingly, emotion's effects on false memory depend on whether it is embedded in the content of to-be-remembered events or in our moods, where mood is an aspect of the context in which events are encoded. We sketch the theoretical basis for this content-context dissociation and then review accumulated evidence that content and context effects are indeed different.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 193 publications
(284 reference statements)
8
96
4
Order By: Relevance
“…In this case, our results showed that negative words were more prominent during free recall than neutral ones. These results are not in line with what is stated on this matter in earlier work (see Bookbinder & Brainerd, 2016;Talmi, Luk, McGarry, & Moscovitch, 2007). In Otgaar and colleagues (2008), for instance, 7-year-olds heard two true and one false story about their school experiences.…”
Section: Discussion and Limitationscontrasting
confidence: 55%
“…In this case, our results showed that negative words were more prominent during free recall than neutral ones. These results are not in line with what is stated on this matter in earlier work (see Bookbinder & Brainerd, 2016;Talmi, Luk, McGarry, & Moscovitch, 2007). In Otgaar and colleagues (2008), for instance, 7-year-olds heard two true and one false story about their school experiences.…”
Section: Discussion and Limitationscontrasting
confidence: 55%
“…In addition, the difference between the present findings and prior research might also be due to arousal caused by the emotional content of the word lists. Arousal of emotional word lists was well controlled in the present study; however, in some prior studies, arousal has often been confounded with valence (for review, see Bookbinder & Brainerd, ). Prior research has indicated that once the arousal level of emotional word lists is controlled across list valence, developmental reversals for positive or neutral word lists tend to be less pronounced than for negative word lists (Brainerd et al., ), a finding that is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Again, this difference is likely due to differences in arousal levels across studies. Prior research has shown that valence and arousal have different effects on false memories (Brainerd et al., ; Bookbinder & Brainerd, ; Corson & Verrier, ). In the present study, we strictly controlled arousal across moods, whereas in prior research, arousal has often been confounded with valence (e.g., Storbeck & Clore, ).…”
Section: Discussionmentioning
confidence: 99%
“…1 | No. 1 summarized in this section, one can conclude that both negative valence and high arousal enhance the generation of false memories (Bookbinder & Brainerd, 2016;Kaplan, Van Damme, Levine, & Loftus, 2016). …”
Section: Psychological Research On Urban Societymentioning
confidence: 99%